-1-4x+7x=1x+4x
-1-4x+7x=1x+4x
-1+-4x+7x=x+4x
(-4x+7x)+(-1)=(x+4x)
3x+-1=5x
3x-1=5x
3x-1-5x=5x-5x
-2x-1=0
-2x-1+1=0+1
-2x=1
-2x/-2=1/2
x=-1/2
Answer:
27
Step-by-step explanation:
C
Step-by-step explanation:
Just got it right
Answer:
Step-by-step explanation:
![V=\frac{4\pi r^3}{4}\\ \\ V=\frac{\pi d^3}{6}\\ \\ V=\frac{\pi 8^3}{6}\\ \\ V\approx 268.1cm^3](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B4%5Cpi%20r%5E3%7D%7B4%7D%5C%5C%20%5C%5C%20V%3D%5Cfrac%7B%5Cpi%20d%5E3%7D%7B6%7D%5C%5C%20%5C%5C%20V%3D%5Cfrac%7B%5Cpi%208%5E3%7D%7B6%7D%5C%5C%20%5C%5C%20V%5Capprox%20268.1cm%5E3)
By intuition, the function of y with respect to x will be:
y = 4x
You can prove this by substitute in each pair of values of x and y
So the constant of relationship is 4